Avifauna de la concesión "cuenca alta del río Itaya" durante la estación lluviosa. Loreto - Perú - Saboya del Castillo, Percy Paolo (2022)
Between March to May 2017, the ornitofauna of the «Cuenca Alta del Río Itaya» Conservation Concession, Universidad Científica del Perú was surveyed. The goals of this study were to describe avian diversity and abundance and the forest conservation status according to the sensitivity of bird species to degraded habitats. Transect surveys, capture of individuals with mist-nets and random records were carried out in this study to record birds. In total, 266 species of birds were identified, distribuend across 19 orders and 45 families. The most diverse families were Thamnophilidae, Tyrannidae, Furnariidae and Thraupidae. For the transect surveys the most abundant species were Thamnomanes caesius, Herpsilochmus gentryi, Pachysylvia hypoxantha, Ramphastos tucanus and Thamnophilus murinus. The results revealed that the research área is remarkably well-preserved, showing a large percentage of birds species and abundances that are highly sensitive to disturbance. A total 22 species of white-sand forest specialists were recorded, two of which (Percnostola arenarum and Zimmerius villarejoi) are endemic to Peru.